Carbon nanotube-reinforced Al alloy-based nanocomposites via spark plasma sintering. (July 2015) - Maiti, A; Reddy, L; Chen, F; Zhang, L; Schoenung, JM; Lavernia, EJ; Laha, T
Carbon nanotubes have emerged as potential reinforcements that can be used to engineer composites with tailored combinations of physical and mechanical properties. In the present study, an Al alloy-based nanostructured composite containing multiwalled carbon nanotubes (MWCNT) as a reinforcement phase has been synthesized by a combination of two novel processing techniques, which are cryomilling and spark plasma sintering. Scanning electron microscopy and quantitative image analysis have been performed to provide insight into the microstructural evolution and to verify the retention of the carbon nanotubes in the consolidated samples. Nanoindentation, microhardness, and tribological studies have been carried out to understand the effect of variation in MWCNT content and processing on the mechanical response of the consolidated nanocomposites. The characterization results affirm the retention of carbon nanotubes and varied improvement in mechanical properties in the nanocomposites. Raman spectroscopy analysis revealed that the MWCNTs were partially damaged during cryomilling.